Understanding Norse Myths - Brian Williams (United States Crabtree Publishing Co,US, 2013)
In this book, readers are introduced to the mythology that reflects the religious beliefs and social practices of the Scandinavian people and the fearsome Vikings. Readers learn about the great Norse gods and the Nine Worlds. They will also discover how the physical geography of Scandinavia influences their mythology.